2019
DOI: 10.19080/adoh.2019.10.555786
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dental Training in Terms of Anxiety Control Among Dental Students-A Quasi Experimental Study

Abstract: The purpose of the study is to evaluate the effectiveness of dental school training in diminishing dental treatment anxiety among dental students of Dow University of Health Sciences OJHA hospital. The study included first year students who were given questionnaire based on Norman Corah Scale. The students were again given same questionnaire in their final year. The scores were calculated in first and final year of their dental school. Data was analyzed using SPSS version 23. Paired t-test was used to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This finding is similar to a study in Brazil, which found that 27.5% of dental students experienced dental anxiety after encountering clinical practices (Serra-negra et al, 2012). Similarly in Pakistan, a study revealed that dental students were afraid to perform dental treatments during their initial years of training (Bari, 2019). Stanford et al had compared the level of dental fear among students of dentistry, psychology and biology, among which dental students were least who elicited dental fear (Serra-negra et al, 2012).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This finding is similar to a study in Brazil, which found that 27.5% of dental students experienced dental anxiety after encountering clinical practices (Serra-negra et al, 2012). Similarly in Pakistan, a study revealed that dental students were afraid to perform dental treatments during their initial years of training (Bari, 2019). Stanford et al had compared the level of dental fear among students of dentistry, psychology and biology, among which dental students were least who elicited dental fear (Serra-negra et al, 2012).…”
Section: Resultssupporting
confidence: 75%
“…Study on anxiety of clinical medical students reported by Moss and McManus showed half of the participants had moderate to severe anxiety states (Moss and McManus, 1992). According to Davidovich et al, a higher number of dental students elicited anxiety and stress during dental treatment when compared to experienced dentists (Davidovich et al, 2015). An online questionnaire conducted in University of Otago had revealed a high prevalence of detrimental emotions among fourth year dental and medical students.…”
Section: Introductionmentioning
confidence: 99%